Possible Real Economic Consequences of Financial Actors’ Attitudes Towards Climate Change and Realized Risks - Málits, Péter; El-Meouch Nedim, Márton; Drabancz, Áron (Public Finance Quarterly, 2022)
The effects of climate change on the real economy are also reflected in the financial system. In this study, we examine the attitudes of key players in the financial system (central and commercial banks) towards the financial risks of climate change, based on the literature in the field. The key players in the financial system, the climate change-specific relationships of the corporate sector and the main channels connecting them are illustrated using a corporate project evaluation model, partly assessing which variables and risks a company should consider when making an investment decision. The results show that climate change can affect the performance of financial institutions in a number of ways, but these risks cannot yet be clearly identified in Hungarian interest rate spreads.